Physical Interaction between Envelope Glycoproteins E and M of Pseudorabies Virus and the Major Tegument Protein UL49 - Fuchs, Walter (American Society for Microbiology, 2002)
Envelope glycoprotein M (gM) and the complex formed by glycoproteins E (gE) and I (gI) are involved in the secondary envelopment of pseudorabies virus (PrV) particles in the cytoplasm of infected cells. In the absence of the gE-gI complex and gM, envelopment is blocked and capsids surrounded by tegument proteins accumulate in the cytoplasm (A. R. Brack, J. Dijkstra, H. Granzow, B. G. Klupp, and T. C. Mettenleiter, J. Virol. 73:5364-5372, 1999). Here we demonstrate by yeast two-hybrid analyses that the cytoplasmic domains of gE and gM specifically interact with the C-terminal part of the UL49 gene product of PrV, which represents a major tegument protein and which is homologous to VP22 of herpes simplex virus type 1. However, deletion of the UL49 gene from PrV had only minor effects on viral replication, and ultrastructural analyses of infected cells confirmed that virus maturation and egress, including secondary envelopment in the cytoplasm, were not detectably affected by the absence of UL49. Moreover, the UL49 gene product was shown to be dispensable for virion localization of gE and gM, and mutants lacking either gE or gM incorporated the UL49 protein efficiently into virus particles. In contrast, a PrV mutant with deletions of gE-gI and gM failed to incorporate the UL49 protein despite apparently unaltered intracytoplasmic UL49 expression. In summary, we describe specific interactions between herpesvirus envelope and tegument proteins which may play a role in secondary envelopment during herpesvirus virion maturation.